The oncologic results of cryoablation in prostate cancer patients with bone metastases. (3rd October 2018) - Si, Tongguo; Guo, Zhi; Yang, Xueling; Zhang, Weihao; Xing, Wenge
Abstract: Objective: To explore the role of whole gland cryoablation plus ADT in prostate cancer (PCa) with bone metastases compared with ADT treatment alone in metastatic PCa. Methods: A total of 30 patients with biopsy-proven PCa with bone metastases underwent cryoablation and ADT treatment. The control group consisted of 30 men who were initially treated with ADT only and who were followed until progression, development of castration resistant PCa or death. Patients were pair matched for age, PSA level, clinical stage, preoperative biopsy Gleason score and bone metastases. Time to clinical progression, time to CRPC, cancer-specific survival and overall survival were analysed using descriptive statistical analysis. Results: Age at diagnosis, baseline PSA, biopsy Gleason score and ECOG status were comparable between the two groups. Prostate cryoablation was well tolerated and no serious complications occurred. At the last follow-up, patients in the cryoablation and ADT treatment group had a lower median PSA nadir (0.4 ng/ml vs. 0.8 ng/ml, p  < 0.01) and longer time to CRPC (33 ± 0.9 mo vs. 22 ± 0.8 mo, p  < 0.01). Further analyses detected the statistically significant benefits of cryoablation treatment not only in PFS (41 ± 1.4 mo vs. 22 ± 0.8 mo, p  < 0.01), but also in CSS (52 ± 1.9 mo vs. 32 ± 2.4 mo, p  ± 0.01) and OS (41 ± 1.5 mo vs. 28 ± 1.7 mo, p  < 0.01). Moreover, there were fewer palliative procedures for local progression in the cryoablation group than the controls. Conclusions: Cryoablation plus ADT might be a treatment option in the multimodality management of metastatic prostate cancer. Further investigations are warranted.